2019
DOI: 10.1149/09401.0041ecst
|View full text |Cite
|
Sign up to set email alerts
|

A Corrosion Inhibition Study of a Novel Nonionic Gemini Surfactant Derived from Palm Oil for Supermartensitic Stainless Steel in Sour Solution

Abstract: In the present investigation a novel non-ionic gemini surfactant, namely bis(2-((2-palmitoamidoetil) amino) etil) 1H-imidazol-4,5-dicarboxilate, was synthesized from the fatty acids contained in the palm oil and evaluated as corrosion inhibitor for UNS S41425 type supermartensitic stainless steel in a sour solution. The obtained results from electrochemical techniques showed that, the inhibition efficiency increased with increase of the inhibitor concentration. The maximum inhibition efficiency was reached 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is well known that when the absolute value of Δ G ads is less than 20, the corrosion inhibitor is physically adsorbed to the metal surface, and when greater than 40, the corrosion inhibitor is chemically adsorbed to the metal surface (Abd El‐Lateef & Khalaf, 2021). Therefore, the Δ G ads value of TMPA denotes that the physical and chemical adsorption are both carried out simultaneously on the metal surface (Anastopoulos et al, 2015; Hernandez et al, 2019; Mandavian et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that when the absolute value of Δ G ads is less than 20, the corrosion inhibitor is physically adsorbed to the metal surface, and when greater than 40, the corrosion inhibitor is chemically adsorbed to the metal surface (Abd El‐Lateef & Khalaf, 2021). Therefore, the Δ G ads value of TMPA denotes that the physical and chemical adsorption are both carried out simultaneously on the metal surface (Anastopoulos et al, 2015; Hernandez et al, 2019; Mandavian et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the q vs fn values corresponding to the steel immersed in the sour solution at different concentrations of the inhibitor during the SSRT test along with the q and fn obtained in static conditions corresponding to the time series reported in a previous work (28). Under static conditions, the q values tended to lower values (10 -6 to 10 -9 C) and fn to higher values (1 to 10 Hz/cm 2 ) as the concentration of the inhibitor increased, which suggests that the presence of the inhibitor protected the metal producing a slight corrosion or pseudopassivation on the surface, especially at 100 ppm.…”
Section: Statistical En Analysismentioning
confidence: 99%
“…Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Comparative study of the inhibitory effects of various parts of plants (leaves, fruits, barks, nuts, and seeds) have been conducted on mild steel, and stainless steel in acidic, alkaline, and neutral media using Gravimetric methods (weight loss), Potentiodynamic polarization (PDP) and Electrochemical impedance spectroscopy (EIS) techniques [43][44][45] . These studies have reported high inhibition e ciencies with inhibition e ciency increasing with increasing inhibitor concentration 40,[48][49][50][51][52][53] .…”
Section: Introductionmentioning
confidence: 99%